Engaging the Voices of Girls in the Aftermath of Sierra Leone's Conflict: Experiences and Perspectives in a Culture of Violence - Denov, Myriam; Maclure, Richard (Anthropologica, 2022)
Despite the protections provided to children under the UN Convention on the Rights of the Child, the issue of child soldiers has become a major global concern. More than 250 000 soldiers under the age of 18 are fighting in conflicts in over 40 countries around the world. During Sierra Leone's decade-long civil war, thousands of children were actively engaged as participants in armed struggle. While there is ample descriptive evidence of the conditions and factors underlying the rise of child soldiery in Sierra Leone and elsewhere in the developing world, most of the literature has portrayed this as a uniquely male phenomenon. Yet in Sierra Leone an estimated 30% of child soldiers in oppositional forces were girls. So far, however, there is a paucity of empirical information that distinguishes the experiences of these girls from those of boys. Drawing on in-depth interviews with 40 Sierra Leonean girls formerly in fighting forces, this paper traces girls' perspectives and experiences as victims, perpetrators and resisters of violence and armed conflict.